Dano oxidativo e atividade imunológica de ratos treinados, suplementados com maltodextrina. - Leite, Cátia Fernandes (2011)
Fatigue can be caused by depletion of carbohydrates and by the action of reactive oxygen species. Thus, carbohydrates are recognized as important to improve performance, minimize the decline in immune activity and reduce oxidative stress. Objective: To assess the occurrence of oxidative damage and abnormal levels of blood leukocytes in trained and sedentary rats supplemented with maltodextrina or water. Methods: Male Wistar rats (60 days) were divided into six groups: sedentary non-supplemented (n = 12) and supplemented (n = 12), trained in EEML - Maximum Lactate Steady State - not supplemented (n = 11) and supplemented (n = 11), trained at high intensity non-supplemented (n = 12) and supplemented (n = 11). The training protocol consisted of 8 weeks of swimming in a continuous pattern in EEML (60min.day-1) or intermittent (two periods of 30 minutes, with an interval of 10min), with loads corresponding to 5% and 10% of body weight,respectively. During 37 days the animals were supplemented with a daily dose of 0.48 g.kg-1 maltodextrin dissolved in water or pure water. Concentrations of blood lactate, hepatic glycogen content and muscle lipid peroxidation, protein oxidation and total and differential leukocytes were measured. Results: Despite the lack of statistical significance in malondialdehyde concentration and total and differential count of leukocytes between the groups, both exercise models have resulted in increases in protein carbonyl (p˂0.001). Aerobic exercise and supplementation with maltodextrin resulted in increased muscle glycogen content when compared to sedentary groups receiving water (p=0.007) or maltodextrin (p=0.008). Conclusions: The exercise did not cause damage to the lipid layers or abnormal levels of circulating leukocytes, however, both standards of training provided important protein loss. Maltodextrin supplementation was effective in sparing muscle glycogen stores during aerobic exercise.